Paper and fire - Caine, Rachel (New York, New York : New American Library, 2016)
"In Ink and Bone, author Rachel Caine introduced a world where knowledge is power, and power corrupts absolutely. Now she continues the story of those who dare to defy the Great Library--and rewrite history ... With an iron fist, the Great Library controls the knowledge of the world, ruthlessly stamping out all rebellion and in the name of the greater good forbidding the personal ownership of books. Jess Brightwell has survived his introduction to the sinister, seductive world of the Library, but serving in its army is nothing like what he envisioned. His life and the lives of those he cares for have been altered forever. His best friend is lost, and Morgan, the girl he loves, is locked away in the Iron Tower, doomed to a life apart from everything she knows. Embarking on a mission to save one of their own, Jess and his band of allies make one wrong move and suddenly find themselves hunted by the Library's deadly automata and forced to flee Alexandria, all the way to London. But Jess's home isn't safe anymore. The Welsh army is coming, London is burning, and soon Jess must choose between his friends, his family, and the Library, which is willing to sacrifice anything and anyone in the search for ultimate control."--
Keywords: Alexandrian Library -- Juvenile fiction; Alexandrian Library; Libraries -- Juvenile fiction; JUVENILE FICTION -- Fantasy & Magic; JUVENILE FICTION -- Action & Adventure -- General; JUVENILE FICTION -- Love & Romance; Libraries; Juvenile works; Alternative histories (Fiction); Dystopian fiction; Alternative histories (Fiction); Dystopian fiction; Fiction; Alternative histories (Fiction); Dystopias